Discovery and Preclinical Development of Orally Active Small Molecules that Exhibit Highly Selective Follicle Stimulating Hormone Receptor Agonism - Nataraja, Selva; Yu, Henry; Guner, Joie; Palmer, Stephen (Frontiers in Pharmacology, 2021)
An orally active follicle stimulating hormone receptor allosteric agonist would provide a preferred treatment for over 16 million infertile women of reproductive age in low complexity methods (ovulation induction-intrauterine insemination) or in high complexity methods (controlled ovarian stimulation-in vitro fertilization). We present two oral follicle stimulating hormone receptor allosteric agonist compounds that have the desired pharmacology, drug metabolism, pharmacokinetics, and safety profile for clinical use. These molecules provide a single agent suitable for ovulation induction-intrauterine insemination or controlled ovarian stimulation-in vitro fertilization that is more convenient for patients and achieves similar preclinical efficacy as rec-hFSH. TOP5668, TOP5300 were evaluated in vitro in Chinese hamster ovary cells transfected with individual glycoprotein receptors measuring cAMP (FSHR, LH/CGR, thyroid stimulating hormone receptor). TOP5668 was found to have solely follicle stimulating hormone receptor allosteric agonist activity while TOP5300 was found to have mixed follicle stimulating hormone receptor allosteric agonist and LHR-AA activity. Both compounds stimulated concentration-dependent increases in estradiol production from cultured rat granulosa cells in the presence or absence of low dose rec-hFSH, while only TOP5300 stimulated testosterone production from rat primary Leydig cells. In pooled human granulosa cells obtained from patients undergoing controlled ovarian stimulation-in vitro fertilization, TOP5300 stimulated 7-fold greater maximal estradiol response than rec-hFSH and TOP5668 was 10-fold more potent than TOP5300. Both TOP5300 and TOP5668 stimulated follicular development in immature rat to the same efficacy as recombinant follicle stimulating hormone. In mice treated with TOP5300, in the presence of low dose of follicle stimulating hormone, there were no differences in oocyte number, fertilization rate, and hatched blastocyst rate in mice with TOP5300 and low dose follicle stimulating hormone vs. reference proteins pregnant mare serum gonadotropin or high dose rec-hFSH. ADME/PK and safety profiles were favorable. In addition, there was no appreciable activity on thyroid hormones by TOP5300 in 14-days toxicological study in rat or dog. The selected lead compound, TOP5300 stimulated a more robust increase in estradiol production from granulosa-lutein cells from women with polycystic ovarian syndrome patient compared to rec-hFSH. Conclusions: Two novel oral FSHR allosteric agonist, TOP5668 and TOP5300, were found to mimic the biological activity of rec hFSH in preclinical studies. Both compounds led to folliculogenesis and superovulation in rat and mice. Specifically, TOP5300 led to a similar number of ovulated oocytes that fertilized and developed into hatched blastocysts in mice when compared to rec-hFSH. The safety profile demonstrated lack of toxicity.